Planning the transport of loads to oil platforms considering the arrangement of the loads on the ship's deck. (May 2018) - Pinto, Gustavo de Luna; Vitorugo, Lirielly Ruela; Rosa, Rodrigo de Alvarenga; Arpini, Bianca Passos; Caprini, Lucas Arrevabene
Highlights: Logistics problem of the major Brazilian oil company. It can be applied to several other oil companies. Financial benefits can be achieved by the oil company. Plan routes integrated with the arrangement of the loads with ship's balance and load's rotation. A Hybrid Simulated Annealing with Ship's Balance (HSA-SB) is proposed to solve the problem. Abstract: Oil exploration in Brazil is done mainly by offshore oil platforms located far from the coast and ships transport all supplies for them. This paper proposes a method based on a Hybrid Simulated Annealing with Ship's Balance (HSA-SB) metaheuristic to plan the transport of loads to offshore platforms considering the arrangement of the loads on the ship's deck and the ship's balance about its keel. The main objective of HSA-SB is to minimize the ships affreightment costs by reducing the number of ships used and the distance sailed. It also arranges the loads on the deck, aiming to reduce ship's imbalance. HSA-SB was tested on real instances from a major Brazilian oil company and the results showed possible financial benefits.